2010
DOI: 10.1021/ja100919d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Monolayer Organosilicon Nanosheets

Abstract: The synthesis of silicon nanosheets for fabricating electronic devices, without using conventional vacuum processes and vapor deposition, is challenging and is anticipated to receive significant attention for a wide range of applications. Here, we report the synthesis of oxygen-free, phenyl-modified organosilicon nanosheets with atomic thickness. In organic solvents, a consequence of this new silicon structure is its uniform dispersion and the possibility of exfoliation into unilamellar nanosheets. Light-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
164
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(179 citation statements)
references
References 14 publications
15
164
0
Order By: Relevance
“…Layered polysilane, Si 6 H 6 , was used as the starting material to produce organic modified SiNSs. Using hydrosilylation 38) or the Grignard reaction, 39) the resulting materials, which were insoluble in water and ethanol, could be dispersed in some organic solvents, such as hexane, chloroform, acetone, and ether. Figure 4(a) shows the attenuated total reflection infrared spectrum of Si 6 H 6 after it was hydrosilylated in 1-hexene.…”
Section: Organic Modifications Of the Nanosheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Layered polysilane, Si 6 H 6 , was used as the starting material to produce organic modified SiNSs. Using hydrosilylation 38) or the Grignard reaction, 39) the resulting materials, which were insoluble in water and ethanol, could be dispersed in some organic solvents, such as hexane, chloroform, acetone, and ether. Figure 4(a) shows the attenuated total reflection infrared spectrum of Si 6 H 6 after it was hydrosilylated in 1-hexene.…”
Section: Organic Modifications Of the Nanosheetsmentioning
confidence: 99%
“…After numerous unsuccessful trials, phenyl-terminated SiNSs (Si 6 H 4 Ph 2 ) were successfully synthesized by reacting Si 6 H 6 with phenyl magnesium bromide. 39) An intermediate halogenation step is usually required to allow organic groups to be introduced into bulk Si(111) using a Grignard reagent because of the low reactivities involved. 41) However, SiNSs were successfully synthesized without an intermediate halogenation step.…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] The studies on the successful synthesis of inorganic functional NSs with thickness of a few nanometers and well-defi ned properties and their mass production or handling strategies, are in progress up to date. [10][11][12][13][14][15][16][17] However, all of these topics are the subject of many actual research activities, with problems which are not yet solved. [18][19][20][21][22] One of the problems to be improved is that NSs' practical electrochemical electrode fabrication remains in a conventional process, in which NSs are mixed with carbon based conductors and organic binder for good mechanical adhesion as well as electrical contact on a current collector.…”
Section: Doi: 101002/adma201102359mentioning
confidence: 99%
“…[11][12][13][14] For instance, Okamoto et al 11,12 demonstrated that organosilicon (Si 6 H 4 Ph 2 ) nanosheets can be fabricated by the chemical reaction of polysilane (Si 6 H 6 ) and a Grignard reagent. This method is useful for forming regularly stacked structures of SiNSs with limited dimensions.…”
Section: Introductionmentioning
confidence: 99%